Promoting the use of ICT and the development of media literacy and citizenship education: the multimedia CD-Rom "Let's produce school newspapers - Tomé, V.; Guilhermina Lobato Miranda; Helena Menezes (Current Developments in Technology-Assisted Education, 2006)
In the 21st century educational tendencies from the 19th century still exist: reading, writing and counting were priorities. However, in the knowledge society, citizens must develop other skills to interact in a world pointed out by the ubiquity of media. To be considered a literate citizen today, it implies to be a critical receiver and a reflexive producer of media messages. Nowadays, media literacy and citizenship education are an urgent matter in education, as the use of ICT in schools. In order to bridge the gap between the use of ICT in schools and in society, and in order to develop critical and reflexive skills in young people, a CD-Rom was developed and tested in two Portuguese schools. The CD-Rom "Let's produce school newspapers" motivates pupils to produce newspapers, to read and write critically and to become better citizens. It was developed under the philosophy of criticizing media through media. This paper provides the theoretical background of media literacy and its importance in the development of citizenship education.